2020
DOI: 10.21127/yaoyigc20190031
|View full text |Cite
|
Sign up to set email alerts
|

Paradox of Late Transition-Metal Catalysts in Ethylene Polymerization

Abstract: Polyolefin materials are the most synthesized polymer used nowadays and symbolize the development level of the national petrochemical industry, in which polyethylenes are major along with alternative product α-olefins for co-monomer and substrates for fine chemicals. Likely operating catalysts such as Ziegler-Natta and metallocene meet all demanding of various polyethylene materials, what is any business in developing late-transition metal catalysts for ethylene reactivity? In the past two decades, we realized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“…Subsequently, the activity gradually decreased to 5.63×10 6 g (PE) mol −1 (Co) h −1 after 1 hour, which indicated that the active species was not only formed quickly following the addition of MAO but also gradually underwent deactivation over the course of time [61] . Nevertheless, it was evident that longer polyethylene chains were produced with longer reaction time (Figure 4), which suggests that there were still sufficient active sites to maintain effective chain propagation [62] …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, the activity gradually decreased to 5.63×10 6 g (PE) mol −1 (Co) h −1 after 1 hour, which indicated that the active species was not only formed quickly following the addition of MAO but also gradually underwent deactivation over the course of time [61] . Nevertheless, it was evident that longer polyethylene chains were produced with longer reaction time (Figure 4), which suggests that there were still sufficient active sites to maintain effective chain propagation [62] …”
Section: Resultsmentioning
confidence: 97%
“…[61] Nevertheless, it was evident that longer polyethylene chains were produced with longer reaction time (Figure 4), which suggests that there were still sufficient active sites to maintain effective chain propagation. [62] To examine the effect of ethylene pressure on Co1/MAO, we additionally conducted the polymerizations at 5 atm and 1 atm. At 5 atm, the catalytic activity dropped by more than half from 8.96 × 10 6 g (PE) mol À 1 (Co) h À 1 to 3.49 × 10 6 g (PE) mol À 1 (Co) h À 1 (entries 3 and 14, Table 2).…”
Section: Catalytic Evaluation For Ethylene Polymerizationmentioning
confidence: 99%
“…With particular regard to late transition metal polymerization catalysts, α-diimine nickel complexes have been central to the development of the field . Indeed, these catalysts, first reported in 1995 ( A in Chart ), have the capacity to mediate the formation of branched polyethylenes from a single ethylene feed via a process known as chain walking .…”
Section: Introductionmentioning
confidence: 99%
“…Recently the area of nickel-catalyzed oligomerization and polymerization of olefins received a new boost. Nickel complexes are being widely employed for processes of chain-walking ethylene polymerization [4,5,[14][15][16][17][18][19][20][21][22][23]6,[24][25][26][27][7][8][9][10][11][12][13] and copolymerization of ethylene with polar monomers [22,24,[35][36][37][38][39][40][41][42][43][44][27][28][29][30][31][32][33][34]. However, the interest in the development of new nickel-based catalytic systems for ethylene oligomerization is still high [4,6,[53][54]…”
Section: Introductionmentioning
confidence: 99%